Analysis of Medical Education Output in Web of Science Database - Maryam Okhovati; Halimeh Sadeghi; Reza Shojaei (Kerman University of Medical Sciences, 2013)
Background & Objective: Knowledge maps graphically draw a branch of science and help to describe it more precisely This research was conducted to study the scientific productivity and collaborative coefficient of medical education authors during 20022011 Methods: This descriptive study was done using scientometric techniques The papers indexed in Web of Science were searched using medical education keywords The retrieved records were entered into Excel and HistCite Citation analysis techniques were used and the map was drawn Results: The rate of productivity was 28% 10123 retrieved records were published in 1506 journals and most were published in Medical Education Journal 5791 educational institutes contributed to publishing papers Van der Vleuten published more papers than other authors The collaborative coefficient was moderate 122 countries contributed to publishing these papers and USA was the most active country Finally 5 clusters were identified including learning methods in medical education job depression the effect of working hour reduction on health services evaluation of professional competency in medical education and the relationship between medical sciences and industry Conclusion: Medical education follows an ascending trend in scientific productivity The results of the current study can be used in future planning and help this field to improve